Pathogenic Mutations Differentially Regulate Cell-to-Cell Transmission of α-Synuclein - Guan, Yuan; Zhao, Xiaofang; Liu, Fengwei; Yan, Shuxin; Wang, Yalong; Du, Cuilian; Cui, Xiuyu; Li, Rena; Zhang, Claire Xi (Frontiers in Cellular Neuroscience, 2020)
Recent studies suggest that the cell-to-cell spread of pathological α-synuclein (α-syn) plays important roles in the development of Parkinson’s disease (PD). PD patients who carry α-syn gene mutations often have an earlier onset and more severe clinical symptoms and pathology than sporadic PD cases who carry the wild-type (WT) α-syn gene. However, the molecular mechanism by which α-syn gene mutations promote PD remains unclear. Here, we hypothesized that pathogenic mutations facilitate the intercellular transfer and cytotoxicity of α-syn, favoring an early disease onset and faster progression. We investigated the effects of eight known pathogenic mutations in human α-syn (A18T, A29S, A30P, E46K, H50Q, G51D, A53E, and A53T) on its pathological transmission in terms of secretion, aggregation, intracellular level, cytotoxicity, seeding, and induction of neuroinflammation in SH-SY5Y neuroblastoma cells, cultured rat neurons, and microglia, and the rat substantia nigra pars compacta. We found that 2 of the 8 mutations (H50Q and A53T) significantly increased α-syn secretion while 6 mutations (A18T, A29S, A30P, G51D, A53E, and E46K) tended to enhance it. In vitro α-syn aggregation experiments showed that H50Q promoted while G51D delayed aggregation most strongly. Interestingly, 3 mutations (E46K, H50Q, and G51D) greatly increased the intracellular α-syn level when cultured cells were treated with preformed α-syn fibrils (PFFs) compared with the WT, while the other 5 had no effect. We also demonstrated that H50Q, G51D, and A53T PFFs, but not E46K PFFs, efficiently seeded in vivo and acutely induced neuroinflammation in rat substantia nigra pars compacta. Our data indicate that pathogenic mutations augment the prion-like spread of α-syn at different steps and blockade of this pathogenic propagation may serve as a promising therapeutic intervention for PD.